Not their first rodeo - Jeffries, Christy (Harlequin special edition, 2021)
The last thing Sheriff Marcus King needs is his past sneaking back into his present. Years ago, Violet Cortez-Hill disappeared from his life, leaving him with unanswered questions--and a lot of hurt. Now the widowed father of twin boys finds himself forced to interact with the pretty public defender daily. Their heartache is mutual--but so is their attraction. Is there still a chance to saddle up and ride off into their future?